2021
DOI: 10.3390/genes12071045
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Characterization of Acetyl Coenzyme A: Diacylglycerol Acyltransferase Genes in Cotton Identify the Roles of GhDGAT3D in Oil Biosynthesis and Fatty Acid Composition

Abstract: Cottonseed oil is rich in unsaturated fatty acids (UFAs) and serves as an edible oil in human nutrition. Reports suggest that acyl-coenzyme A: diacylglycerol acyltransferases (DGAT) and wax ester synthase/DGAT (WSD1) genes encode a key group of enzymes that catalyze the final step for triacylglycerol biosynthesis and enable an important rate-limiting process. However, their roles in oil biosynthesis and the fatty acid profile of cotton seed are poorly understood. Therefore, the aim of this study was to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 65 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…The S. hispanica genome contains an increased number of tandem‐duplicated SAD genes that are upregulated in reproductive tissues, leading to abundant production of PUFAs. This may represent an adaptive response to environmental stress, as seen in other plants (J. Chen et al., 2023; Feng et al., 2017; Zhao et al., 2021). The ShSAD2 and ShSAD7 genes in S. hispanica are overexpressed in response to cold stress (Xue et al., 2023).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The S. hispanica genome contains an increased number of tandem‐duplicated SAD genes that are upregulated in reproductive tissues, leading to abundant production of PUFAs. This may represent an adaptive response to environmental stress, as seen in other plants (J. Chen et al., 2023; Feng et al., 2017; Zhao et al., 2021). The ShSAD2 and ShSAD7 genes in S. hispanica are overexpressed in response to cold stress (Xue et al., 2023).…”
Section: Discussionmentioning
confidence: 96%
“…In S. indicum , a combination of lipid transfer gene family expansion due to tandem duplication and contraction of lipid degradation genes was identified as driving the high accumulation of FAs in seeds (L. Wang et al., 2014). The highly conserved domains in segmental and tandem duplicated wax ester synthase ( WSD1 ) and DGAT genes in Gossypium hirsutum (cotton) were related to a rate‐limiting process during high unsaturated FAs accumulation in seeds (Zhao et al., 2021). The expansion of GmFAD2 genes in Glycine max (soybean) (Lakhssassi et al., 2021) and OeB3 genes in Olea europaea (olive) (Qu et al., 2023) was associated with tandem duplications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DGAT2 from some species is reported to contribute to the accumulation of unusual fatty acids such as a hydroxy fatty acid (ricinoleic acid) in castor bean (Ricinus communis) (Burgal et al, 2008;Cagliari et al, 2010;Kroon et al, 2006;Regmi et al, 2020;Shockey et al, 2019;Troncoso-Ponce et al, 2011), a conjugated fatty acid (αeleostearic acid) in tung tree (Vernicia fordii) (Shockey et al, 2006), and an epoxy fatty acid (vernolic acid) in Vernonia (Vernonia galamensis) (Li et al, 2010b). DGAT1 and DGAT2 are ER membrane-bound, whereas DGAT3 is a soluble cytoplasmic enzyme identified in peanuts (Arachis hypogaea) (Saha et al, 2006), Arabidopsis thaliana (Hernandez et al, 2012), and upland cotton (Gossypium hirsutum) (Zhao et al, 2021). A fourth type of DGAT has a sequence similar to DGAT2 and has both wax ester synthase (WS) and DGAT activity (WS / DGAT) (Kalscheuer and Steinbuchel, 2003;King et al, 2007;Li et al, 2008;Rosli et al, 2018;Xu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A fourth type of DGAT has a sequence similar to DGAT2 and has both wax ester synthase (WS) and DGAT activity (WS / DGAT) (Kalscheuer and Steinbuchel, 2003;King et al, 2007;Li et al, 2008;Rosli et al, 2018;Xu et al, 2021). The most common DGAT is type 1 (DGAT1), which contributes to most of the TAG synthesis in higher plants (Chen et al, 2016;Sanjaya et al, 2013;Xu et al, 2018a), but DGAT2 plays a major role in castor bean (Burgal et al, 2008;Kroon et al, 2006;Troncoso-Ponce et al, 2011) and tung tree (Shockey et al, 2006), and DGAT3 is expressed highly in upland cotton (Zhao et al, 2021). Many studies have reported that increased expression of the DGAT1 gene increases oil content (Andrianov et al, 2010;Lardizabal et al, 2008;Rao and Hildebrand, 2009;Taylor et al, 2009).…”
Section: Introductionmentioning
confidence: 99%